2015
DOI: 10.1002/ejic.201403027
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Hydrogen Production from Aqueous‐Phase Methanol Dehydrogenation with Ruthenium Pincer Complexes Under Mild Conditions

Abstract: A density functional theory (DFT) study was performed to unveil the nature of dihydrogen (H 2 ) production from aqueous-phase methanol dehydrogenation catalyzed by a ruthenium pincer complex. Three catalytic cycles of methanol, formaldehyde, and formate dehydrogenations were investigated at the ωB97X-D/BSI level. The calculated results indicate that the methanol-assisted hydrogen-release step is much more favorable than the direct hydrogen-release one. The dehydrogenation step, the methanol-assisted hydrogenre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 62 publications
2
37
2
1
Order By: Relevance
“…Our computed reaction energy (2.31 kcal/mol) of H 2 elimination ( 1Ru = 2Ru + H 2 ) at B3PW91 differs from that of Yang using the M06‐SCRF (11.8 kcal/mol) as well as those of Gusev et al, at mPW1K‐SCRF (18.8 kcal/mol) and at PBE0‐SCRF (15.4 kcal/mol) or that of Lei et al, using wB97X‐D‐SCRF (7.6 kcal/mol). Considering that 1Ru and 2Ru have been used as effective catalysts for hydrogenation and dehydrogenation, the B3PW91, B3LYP, and BP86 results sound much more reasonable, while those at M06‐SCRF, mPW1K‐SCRF, BPE0‐SCRF, and wB97X‐D‐SCRF as well as B3PW91‐SCRF are less reasonable.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…Our computed reaction energy (2.31 kcal/mol) of H 2 elimination ( 1Ru = 2Ru + H 2 ) at B3PW91 differs from that of Yang using the M06‐SCRF (11.8 kcal/mol) as well as those of Gusev et al, at mPW1K‐SCRF (18.8 kcal/mol) and at PBE0‐SCRF (15.4 kcal/mol) or that of Lei et al, using wB97X‐D‐SCRF (7.6 kcal/mol). Considering that 1Ru and 2Ru have been used as effective catalysts for hydrogenation and dehydrogenation, the B3PW91, B3LYP, and BP86 results sound much more reasonable, while those at M06‐SCRF, mPW1K‐SCRF, BPE0‐SCRF, and wB97X‐D‐SCRF as well as B3PW91‐SCRF are less reasonable.…”
Section: Resultscontrasting
confidence: 55%
“…Nevertheless, CO dissociation energies are much higher than the H 2 elimination barriers, and outer sphere hydrogenation mechanisms are favorable as discussed below. For M 5 Ru, the reported H 2 elimination barrier of 1Ru by Yang [5,6] using M06-SCRF (29.5 kcal/mol) and by Gusev et al, [17]] using mPW1K-SCRF (29.2 kcal/mol) as well as by Lei et al, [16] using wB97X-D-SCRF (27.1 kcal/mol) are much higher than our values (21.07 kcal/mol). For M 5 Os, the reported H 2 elimination barrier of 1Os by Gusev et al using mPW1K-SCRF (30.9 kcal/ mol) is also much higher than our value (23.91 kcal/mol).…”
Section: M and 2m Interconversioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In the same year, Beller and co‐workers found methanol could react with water to produce hydrogen and carbon dioxide at low temperatures through the cooperation of Ru—N unit in the PNP pincer ruthenium complex (PNP)Ru(CO)H (Scheme b) . Theoretical studies suggested that the methanol could assist the hydrogen release step via a “methanol bridge” …”
Section: Background and Originality Contentmentioning
confidence: 99%
“…All calculations were carried out by DFT method with the ωB97X‐D in gas phase using Gaussian 09 program . The hybrid density functional ωB97X‐D method is reliable and used in previous work [7a,18]. The LANL2DZ basis sets were employed for Ir atom, and the 6‐31G(d,p) basis sets were employed for all the other atoms .…”
Section: Computational Detailsmentioning
confidence: 99%